PENYALAHGUNAAN KEWENANGAN JABATAN NOTARIS ATAS PELEPASAN HAK ATAS TANAH UNTUK PENGADAAN TANAH PEMERINTAH DIKAITKAN DENGAN TINDAK PIDANA KORUPSI - Rachmawati; Maryano; Wira Franciska; Rachmawati Rachmawati; Maryano Maryano (Bajang Institute, 2026)
The role of a Notary basically is not only to express the will of the parties in an authentic deed, but also to provide legal opinions for the parties, in order to prevent conflicts or disputes from occurring in the future. Notaries in carrying out their positions cannot commit arbitrary acts, because the Notary's actions are limited by the Law of the Republic of Indonesia Number 2 of 2014 concerning Amendments to the Law of the Republic of Indonesia Number 30 of 2004 concerning the Position of Notary (hereinafter referred to as